PEMBELAJARAN ROBOTIK UNTUK MEMPERSIAPKAN GENERASI MUDA MENGHADAPI REVOLUSI INDUSTRI 4.0 DAN SOCIETY 5.0 - Faridawati, F Faridawati; Minarto, Eko; Istiana Wati, Ika; Sutrisno, Sutrisno; Hakim, Lukman (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2020)
The basic difference between the Industrial revolution 4.0 and society 5.0 is that in the era of the industrial revolution 4.0 technology and computers are used in all human activities, while the era of society 5.0 is an era in which technology becomes a part of humans themselves. The internet is no longer a source of information, but is used to live life. To prepare the young generation to face all the challenges that arise in the era of industrial revolution 4.0 and society 5.0, it is necessary to work hard for educational institutions to educate their students to be ready to face the changing times, and this must start from the most basic level of education, namely at elementary school level (SD and SMP). For this reason, this community service program was arranged, namely improving the quality of education by providing robotic learning training for supervisory teachers and elementary school (SD) students so that they become a generation ready to face all the challenges of the industrial revolution era 4.0 and the society 5.0 era